Istī’ābu al-mufradāt al-Arabīyah abra kitābi Turjumānu al-Qur’ān fī al-Madrasah al-Furqān al-wusthā Jember - Abicandra, Muh. Nidom Hamami; Sa’diyah, Miftahus (Faculty of Tarbiyah and Teacher Training, IAIN Jember, 2021)
Vocabulary was an important component of the language as it contained on it the meanings and use of words in the language from the speaker himself or the writer. One of the methods used to teach Arabic vocabulary in the public middle school Al-Furqan Jambar is to use the book “Tarjoman of the Qur’an, meaning a phrase about the course used in the recitation and memorization program of the Qur’an for the applicants. According to the curriculum of my mother in Surabaya. From this book, everything benefits from understanding the Arabic vocabulary used to understand the Qur’an and its meanings. This research aims 1) to know the process of memorizing Arabic vocabulary through the book “Tarjoman of the Qur’an” Public Intermediate School Al-Furqan Jumper 2) To find out the problem of teaching Arabic vocabulary memorization through the book of Qur’an translators in the public middle school Al Furqan Jumper. As for the research approach that the researcher used, it is the qualitative entrance with the type of field research, and the method of data collection used is the documentary method, the observation and the personal interview. As for the results obtained by the researcher, they are: 1) The process of teaching Arabic vocabulary memorization through the Qur'an translator book depends on a method called “Umayy”, which is the course curriculum used in the public middle school Al Furqan, where the step consisting of seven steps was applied The educational process is as follows: opening and perception by coherence, consolidating the concept, understanding the concept, practice / skills, evaluation and seals. To facilitate the process of memorizing vocabulary for students, tones were used in teaching the Qur’an translators. 2) One of the problems that students face when memorizing Arabic vocabulary is that they do not carry Arabic while teaching the Quran. In addition, when the holiday came, the students' memorization worsened and he was unable to repeat it until the teacher needed to give them the opportunity to repeat memorization as much as the week.